An Overview of the Life Cycle, Reproduction and Factors Influencing Recruitment Success of Tropical Oysters - Joanna W. Doinsing; Julian Ransangan (Ain Shams University, Cairo, Egypt, 2022)
The aquaculture of tropical oysters is a valuable prospective seafood industry. The extremely rapid growth rates of tropical oysters make them attractive to aquaculture candidates. Hence, fundamental knowledge of the biology, life cycle, reproduction and factors affecting recruitment is essential for the successful aquaculture development of these species. This paper attempted to provide an overview of the current knowledge of early embryonic and larval development, and the factors affecting the sex determination, gametogenesis, settlement, and the recruitment success of tropical oysters, as well as the effects of climate change on the recruitment success. Closed culture, stock restocking, stock enhancement, and sea ranching are among the efforts that can be implemented to boost the recruitment success of these valuable species.